2013
DOI: 10.1155/2013/957480
|View full text |Cite
|
Sign up to set email alerts
|

Capillaroscopy in Psoriatic and Rheumatoid Arthritis: A Useful Tool for Differential Diagnosis

Abstract: Impairment of capillaries permeability and changes of microcirculation are associated with inflammatory arthritis. In order to demonstrate microvascular differences between psoriatic arthritis (PsA) and rheumatoid arthritis (RA) we analyzed capillaroscopic abnormalities such as megacapillaries, haemorrhages, ramifications, and avascular areas in patients affected by these two rheumatic disorders. Moreover to identify specific capillaroscopy patterns we analyzed the following parameters: venous limb diameter, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
34
1
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 19 publications
6
34
1
7
Order By: Relevance
“…Although the pathogenesis of nail fold vascular changes in RA is still not completely clear, it has been supposed that inflammation may play a key role . The results of our dermoscopic study are consistent with what was demonstrated by videocapillaroscopy, with obvious differences related to the diverse magnification used in these two techniques (×10 for manual dermoscopy and ×50–1000 for videocapillaroscopy) . In particular, it is possible to speculate that the absence of normal capillary loops in our PsA and RA patients likely reflects the reduction in capillary density/size visible using capillaroscopy, while the presence of sparse dotted vessels in PsA and parallel small vessels/irregular, ramified, blurry, purple vessels in RA could respectively correspond to coiled capillaries and short parallel loops in a fish school‐like pattern/subpapillar venous plexus visibility detectable at higher magnification.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Although the pathogenesis of nail fold vascular changes in RA is still not completely clear, it has been supposed that inflammation may play a key role . The results of our dermoscopic study are consistent with what was demonstrated by videocapillaroscopy, with obvious differences related to the diverse magnification used in these two techniques (×10 for manual dermoscopy and ×50–1000 for videocapillaroscopy) . In particular, it is possible to speculate that the absence of normal capillary loops in our PsA and RA patients likely reflects the reduction in capillary density/size visible using capillaroscopy, while the presence of sparse dotted vessels in PsA and parallel small vessels/irregular, ramified, blurry, purple vessels in RA could respectively correspond to coiled capillaries and short parallel loops in a fish school‐like pattern/subpapillar venous plexus visibility detectable at higher magnification.…”
Section: Discussionsupporting
confidence: 88%
“…Microvascular involvement may represent an early abnormality in both PsA and RA, with possible abnormalities of the vessels of synovial membrane, skin and/or nail fold . Over the last years, nail fold vascular plexus changes have been widely investigated by videocapillaroscopy in both these conditions .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…a diminution in the capillary bed density in the nailfold of psoriatic patients with associated nail changes or DIP (distal interphalangeal predominant) joint disease [24]. The same authors were also of the opinion that NVC could be helpful in differentiation between PsA and rheumatoid arthritis (RA) in which the venous, arterial and loop diameters were significantly higher than in PV, PsA and controls [29].…”
Section: Discussionmentioning
confidence: 99%